BEH 2016
DOI: 10.15208/beh.2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Toward of the spatiality of the ICT sector: Case study from the Slovak Republic

Abstract: Rapid diffusion of ICT has produced significant changes in the way and place for the production of goods and provides services. This implies that ICT had an impact on the industrial structure and geographical location of regions. The ICT industry in the Slovak Republic has been one of few industries in which the employment has continuously grown and this sector has the lowest unemployment rate of all sectors of the economy and permanently grows. All these findings have caused the author to measure the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Madudova and Kolarovszki (2016), Madudova (2016;, and Stalmasekova, Genzorova and Corejova (2017) confirmed that this primacy is largely influenced by the progressing of sub-divisions 62 Computer Programming and 63 Information Services. Sub-divisions 62 and 63 of the ICT sector have also been evaluated because they showed the highest increase and sustainability potential in the future [28][29][30][31].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Madudova and Kolarovszki (2016), Madudova (2016;, and Stalmasekova, Genzorova and Corejova (2017) confirmed that this primacy is largely influenced by the progressing of sub-divisions 62 Computer Programming and 63 Information Services. Sub-divisions 62 and 63 of the ICT sector have also been evaluated because they showed the highest increase and sustainability potential in the future [28][29][30][31].…”
Section: Introductionmentioning
confidence: 91%
“…Sub-divisions 62 and 63 of the ICT sector have also been evaluated because they showed the highest increase and sustainability potential in the future [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The investment of information and communications technology (ICT) sector of Turkey is assessed to be about $30.3 billion in 2011, with a massive increase since 1970s as a result of the rapid international development in the communications and information technologies. Not only ICT sector has a direct impact on the industrial structures and geographical locations of the regions (Madudova, 2016), but also it has been noticed that with each single unit of growth of ICT rises, 1.8 unites of growth rise will be in the whole economy (YASED, 2012). Compliance with such a huge investment and the market integration of ICT sector, the analysis and evaluation of its financial performance is very important.…”
Section: Introductionmentioning
confidence: 99%
“…The most visible and probably most popular medium is the TV. TV as a medium for advertising is especially suitable for an introducing of a product; it allows using picture, sound, music, and movement (Madudova & Kolarovszki, 2016). Thus, the marketing message can be made very emotional and impressive by means of TV.…”
Section: Introductionmentioning
confidence: 99%